Use fly ash for the production of lightweight building materials - Tran Thi, Lan; Nguyen Anh, Duong; Phan Luu, Anh; Tran Thi, Man (Vietnam Journal of Earth Sciences, 2021)
Fly ash is a waste byproduct of thermal power plants or steel plants with a low density. Study on using fly ash to produce lightweight construction materials will is a new application of this material resource. Pha Lai fly ash is a byproduct from Pha Lai Thermal Power Joint Stock Company, in which the main mineral component was mullite (15-20%), quartz (14-16%), carbon (5-7%). The content of the amorphous component was about 67-73%. The chemical composition of Pha Lai mainly was SiO2 (51.73%), Al2O3 (23.22%), Fe2O3 (4.23%). To fabricate the lightweight material from Pha Lai fly ash, the fly ash was mixed with additive materials to create binders following two ways: (1) lime + fly ash and (2) geopolymer technology. For the way of lime + fly ash, with the optimal mixture ratio was fly ash:lime: water = 10:2:1, the lightweight material samples had the bulk density of 1.32g/cm3, the compressive strength of 3.91 MPa, satisfied the Vietnamese standard TCVN 6477-2011 for concrete bricks. Applying the geopolymer technology, with the optimal mixture ratio was fly ash: NaOH/Na2SiO3: Al powder = 100:45:0.15, NaOH/Na2SiO3 ratio = 1:2, the lightweight materials obtained the bulk density of 0,62g/cm3, the compressive strength of 1,54 MPa, satisfied the Vietnamese standard TCVN:9029-2017 for Lightweight concrete - Foam concrete and non-autoclaved concrete products-specification.